A inclusão digital nas salas de aula: avaliação da informatização nas escolas municipais de Belo Horizonte - Georgea Fonseca de Choucair Ramos (2010)
The federal government, in partnership with states and municipalities, has developed various plans and projects for the distribution of computers in public schools in Brazil, aiming to bring teachers and students to the universe of information and promote digital inclusion in educational institutions. Digital inclusion, however, is not a simple issue that is solved by providing computers and means not only physicalconnection and access to either hardware or software. It also depends on how this technology wil meet the needs of society acess to information. Digital inclusion only gain meaning by introducing in its concept, the ability to cope with the immensity of information generated by computers. This study examined the process of using the computer labs of the basic education at the local schools in Belo Horizonte, focusing on the students of the third cycle (13-16 years). The technological environment has brought a great challenge for teachers and students: how to handle the large and growing amount of available information? Educational institutions and teachers are rethinking their teaching practices and upgrading the teaching plans to digital format? The work was done with the development of literature and exploratory searchs. At first, weinvestigated the concept of digital inclusion. We also made a comparison between plans, projects and programs, since many of these concepts have been treated as policies. The second procedure used was a field survey and data collection with schoolmasters, teachers, students and young learners of basic education in municipal schools. With the data obtained, it was possible to evaluate the process of computerization in schools.